2003
DOI: 10.1182/blood-2003-05-1428
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for adequate thymic function but impaired naive T-cell survival following allogeneic hematopoietic stem cell transplantation in the absence of chronic graft-versus-host disease

Abstract: Allogeneic hematopoietic stem cell transplantation (AHSCT) leads to a prolonged state of immunodeficiency characterized by low peripheral naive T-cell counts. To identify the mechanisms leading to this defect we quantitatively and qualitatively analyzed thymic function through quantification of T-cell receptor excision circle (TREC) frequencies (both the signal-joint TREC [sjTREC] and 6 different D␤J␤ TRECs, by-products of T-cell receptor [TCR] ␣ and ␤ gene rearrangement, respectively), in conjunction with imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 56 publications
6
56
0
3
Order By: Relevance
“…Several reports, using phenotypic lymphocyte analysis and/or TRECs quantification, have shown the association between GvHD and delayed T-cell reconstitution after transplantation. [57][58][59][60][61][62] GvHD can affect T-cell recovery in several different ways. First, a number of investigators have shown that GvHD induces thymic dysplasia associated with thymic involution, depletion of cortical and medullary thymocytes, epithelial cell destruction, and loss of Hassall's bodies, which collectively result in T-cell lymphopenia and a failure of negative selection of potentially autoreactive T cells.…”
Section: Graft-vs-host Diseasementioning
confidence: 99%
“…Several reports, using phenotypic lymphocyte analysis and/or TRECs quantification, have shown the association between GvHD and delayed T-cell reconstitution after transplantation. [57][58][59][60][61][62] GvHD can affect T-cell recovery in several different ways. First, a number of investigators have shown that GvHD induces thymic dysplasia associated with thymic involution, depletion of cortical and medullary thymocytes, epithelial cell destruction, and loss of Hassall's bodies, which collectively result in T-cell lymphopenia and a failure of negative selection of potentially autoreactive T cells.…”
Section: Graft-vs-host Diseasementioning
confidence: 99%
“…6 The number of RTE exported to the periphery is determined by the amount of proliferation which occurs between β-and α-chain rearrangement. 7,8 Normal human T-cell development appears to be broadly similar. 9,10 The information about T-cell neogenesis after stem cell transplantation in humans is much more limited because peripheral blood is the only readily accessible compartment for study and this blood contains only 2% of the body's T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is possible that reduction in size of the T naive and T CM CD8 subsets in cGVHD might be the consequence of the reduced production of naive recent thymic T-cell emigrants and/ Letters to the Editor or impaired survival in the periphery, 6 the mechanisms leading to the increase of CD8 T EMRA cells are unknown.…”
mentioning
confidence: 99%
“…5 Recently, a specific activating mutation of the JAK2 tyrosine kinase was detected in 154/201 cases of polycythemia vera (77%), in 21/44 cases of idiopatic myelofibrosis (48%) and in 50/144 cases of essential thrombocythemia (35%). 6,7 The JAK2V617F mutation was subsequently observed only sporadically in 3/119 cases of chronic myelomonocytic leukemia, including a case with a history of B cell lymphoma, and in 5/101 cases of MDS including four patients with a normal karyotype. 8 In our systematic search for genetic abnormalities in t-MDS and t-AML and their association to clinical parameters and cytogenetic characteristics, we examined 140 unselected patients with t-MDS or t-AML previously examined for mutations in the RTK/RAS-BRAF pathway 5 for the JAK2V617F mutation.…”
mentioning
confidence: 99%